2002
DOI: 10.1034/j.1600-0889.2002.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and annual variations in the photosynthetic productivity and carbon balance of a central Siberian pine forest

Abstract: We present a first analysis of data (June 1998 to December 2000) from the long‐term eddy covariance site established in a Pinus sylvestris stand near Zotino in central Siberia as part of the EUROSIBERIAN CARBONFLUX project. As well as examining seasonal patterns in net ecosystem exchange (NE), daily, seasonal and annual estimates of the canopy photosynthesis (or gross primary productivity, GP) were obtained using NE and ecosystem respiration measurements. Although the forest was a small (but significant) sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 68 publications
(125 reference statements)
3
80
2
Order By: Relevance
“…The absorbed PAR during the growing season seems to be well related to P g for all sites. The P g values found here are slightly higher than those for the pine forest in Huhus in Finland where the range for the years 1999-2002 was À692 to À1084 g C m À2 year À1 and also much higher compared to the Siberian pine forest which had ca À600 g C m À2 year À1 (Lloyd et al 2002). The Siberian forest has a shorter growing season, which probably explains its lower P g since the daily incoming radiation during the growing season is similar to our sites.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The absorbed PAR during the growing season seems to be well related to P g for all sites. The P g values found here are slightly higher than those for the pine forest in Huhus in Finland where the range for the years 1999-2002 was À692 to À1084 g C m À2 year À1 and also much higher compared to the Siberian pine forest which had ca À600 g C m À2 year À1 (Lloyd et al 2002). The Siberian forest has a shorter growing season, which probably explains its lower P g since the daily incoming radiation during the growing season is similar to our sites.…”
Section: Discussioncontrasting
confidence: 73%
“…Thus, the proportion of P g lost as autotrophic respiration is on average 63%. This is comparable to other boreal forests in Canada (Ryan et al 1997) and Siberia (Lloyd et al 2002). The fraction of P g going into total biomass varied between 0.12 and 0.25 (Table 4) with the average being 0.17.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…4). Throughout most of the winter, snow covers the ground and both autotrophic and heterotrophic respiration may be limited due to constraints on photosynthesis (e.g., Lloyd et al 2002;Monson et al 2002) and subsequent limitations in labile carbon substrates for decomposers (e.g., Brooks et al 2004, Mission et al 2006. Thus, although temperature may limit respiration processes in the winter, it is clear from this and previous studies at our site (e.g., Ma et al 2005) that moisture-availability is a greater influence on R s throughout the growing season in this Sierran mixed-conifer forest (Fig.…”
Section: Precipitation Effects On R S In Undisturbed Forestmentioning
confidence: 99%
“…The IEA study found that globally, urban area accounts for 67% of energy consumption and 71% of CO 2 emission worldwide (IEA, 2008). Previous researches showed that the carbon flow balance condition of forest ecosystem had an important feedback on global warming (Cox et al, 2000), and the contribution of forest ecosystem in global carbon balance has gained a growing focus from the research world (Lloyd et al, 2002;Kolari et al, 2004). Thus, the importance of urban vegetation to human world was quite obvious.…”
Section: Introductionmentioning
confidence: 98%